Economic Crisis and its Impact on Sustainable Urban Transport - Botzoris, George N. (International Journal of Economics and Financial Issues, 2019)
The paper examines the impact of the Greek economic crisis (2009-2018) and the resulted personal income reduction on the change of commuters’ travel behavior. The analysis is based on an extensive questionnaire survey, which took place in six Greek cities representing 49.5% of the total urban population of the country. The questionnaire survey was conducted during the year 2017 on a random sample of 2,218 individuals through personal interviews. The aim of the questionnaire survey was to draw useful and practical solutions which would reveal the actual effect of the economic crisis on commuters’ travel behavior and their decision to change transport mode for utilitarian or recreational trips, by comparing the years 2008, the year before the beginning of the economic crisis, and the year 2017 when the Greek crisis reached its end. It can be conducted that the personal income reduction has a side effect on the use of private vehicles in favor of the use of public transport and of walking; thus, the crisis has a positive impact on sustainable mobility by changing the way commuters travel in urban areas and favoring more friendly transport modes from both economic and environmental point of view. The results of this survey can be a useful tool for city planners to encourage sustainable transportation so as to increase the quality of life in cities and decrease transport infrastructure investments, energy consumption and environmental degradation. Keywords: Economic Crisis, Personal Income, Commuters Behavior, Transportation, Sustainability JEL Classifications: G01, O18, R41, R42 DOI: https://doi.org/10.32479/ijefi.8868